Prevalence of anti-hepatitis C antibodies and its co-infection with HIV in rural Cameroon - Valirie Ndip Agbor; Claude Tayou Tagny; Jules-Bertrand Kenmegne; Bih Awazi; Charlotte Ngansop; Dora Mbanya; Nicaise Ndembi (BMC Research Notes, 2018)
Abstract Objective To evaluate the prevalence of the co-infection between the human immunodeficiency virus (HIV) and hepatitis C virus (HCV), and the prevalence of factors associated with HCV transmission in a rural Cameroonian community. Results The mean age of the 174 participants included in the study was 30.3 (standard deviation = 13.26) years (age range 12–77 years). the prevalence of HCV/HIV co-infection was 1.7% [95% confidence interval (CI) 1.1–5.9]. The prevalence of HCV and HIV were 6.3% (95% CI 2.9–10.3) and 6.9 (95% CI 5.2–11.3), respectively. Histories of scarification (62.1%), multiple sex partners (31.0%) and sexually transmitted diseases (66.1%) were the most common risk factors of HCV transmission in this study.